A study of risk factors affecting outcome of retinopathy of prematurity: a cross-sectional study at tertiary care centre - Rathod, Hamendrasinh K.; Shah, Maulik; Borkhatariya, Sejal D.; Mandal, Dhaneshwar Kumar (International Journal of Contemporary Pediatrics, 2025)
Background: Retinopathy of prematurity (ROP) remains a significant cause of preventable blindness in premature infants. This study aimed to analyze various risk factors affecting ROP outcomes in a tertiary care setting. Methods: A cross-sectional study was conducted at the Neonatal Care Unit of Guru Gobindsingh Government Hospital and Shri M.P. Shah Government Medical College, Jamnagar, over 10 months, enrolling 180 newborns with ROP. Risk factors were analyzed using descriptive statistics and Chi-square tests, with p<0.05 considered statistically significant. Results: The study identified several risk factors significantly associated with progression to severe ROP requiring intervention: early gestational age, lower birth weight, neonatal sepsis, respiratory distress syndrome, oxygen requirement >7 days, and blood transfusion. Among these, neonatal sepsis, respiratory distress, and prolonged oxygen requirement were identified as preventable factors. Conversely, antenatal steroid administration, exclusive breastfeeding, and surfactant use were associated with decreased ROP severity. Conclusions: While factors like sepsis, prolonged oxygen requirement, low birth weight, respiratory distress syndrome, and blood transfusions were associated with more severe ROP stages, protective factors included exclusive breastfeeding, antenatal steroids, and surfactant use. This understanding can help develop targeted preventive strategies and improve outcomes in premature infants at risk for ROP.